Equilibrium states for impulsive semiflows - Maria Pires de Carvalho (2017)
We consider impulsive semiflows defined on compact metric spaces and give sufficient conditions, both on the semiflows and the potential functions, for the existence and uniqueness of equilibrium states. We also generalize the classical notion of topological pressure to our setting of discontinuous semiflows and prove a variational principle.